Conditional probability of hitting anti-aircraft missile system by anti-radar-guided missile - Kudriashov, V.Ye.; Rozhkov, M.I.; Tkachenko, A.Yu.; Chervonyak, Yu.P. (Radiotekhnika, 2018)
A variant of determining values of the conditional probability to defeat the air defense missile system (ADMS) by the anti-radar missile (ARM) with a passive radar homing head (PRHH) is offered. The detection ranges of the ARM by the ADMS radar are given for various conditions. Both the ARM to ADMS approach time and the ARM to ADMS homing errors standard deviations are given. The probabilities of passing of ARM in ’tube’ of given radius are determined and analyzed. The numerical simulation results of the conditional probability to defeat the ADMS are presented for various application conditions of the ADMS. This allows forming the directions of the ADMS survivability improvement against the PRHH ARM.